PRACTICAL PROBLEMS IN THE FIELD OF LEGAL PROTECTION OF LABOR IN UKRAINE - Chernega , R. (Київський національний університет імені Тараса Шевченка, 2019)
In the article the current state of labor security is investigated. The shortcomings and gaps of thelegislation in the specified area have been identified. The list of practical problems in the field of legalprotection of labor protection is formulated. The author's suggestions for their solution have beendeveloped

У статті досліджено сучасний стан правового забезпечення охорони праці. Виявленонедоліки та прогалини законодавства у вказаній царині. Сформульовано перелік практичнихпроблем у сфері правового забезпечення охорони праці. Розроблено авторські пропозиції щодо їхвирішення.
PRACTICAL PROBLEMS IN THE FIELD OF LEGAL PROTECTION OF LABOR IN UKRAINE
Keywords: problems; legal support; labor protection; labor activity; employee; проблеми; правове забезпечення; охорона праці; трудова діяльність; працівник.